Resilience in the School Environment: Preliminary Studies on Perception of Family and School Aspects among Children from Socially Vulnerable Contexts - Canto, Daniela; Morelato, Gabriela; Greco, Carolina (Pensando Psicología, 2013)
The purpose of this work is to analyze variables associate with perception of the family among a 61-student sample (30 with a history of school failure and 31 without), from vulnerable neighborhoods of Mendoza, Argentina. We evaluated the families’ interrelationship perception, and the evaluation of teachers’ perceptions of their students’ academic strength and performance. The results showed no significant differences between the two groups in terms of the perception of families’ positive and negative aspects. However, it was evident that children with a history of school failure had fewer positive emotions, expressed a vague concept of the family and were more inclined to identify with low value characters than those who had never been left back. Regarding teachers’ perception, the study found an association between the perception of strength and academic performance evaluation among children who had no history of school failure.
Keywords: family; school failure; resilience; social vulnerability